More Choosy for Minor Foods: Diet, Seasonality and Food Selection in Sympatric Frugivorous and Folivorous Lemurs - Mitchell T. Irwin; Vololonirina Rahalinarivo; Bruno Ramorasata; Jean‐Luc Raharison; Jean‐Freddy Ranaivoarisoa; Chloé N. M. Gherardi; Jessica M. Rothman (Ecology and Evolution)
ABSTRACT Despite traditional dietary categories common in primatology (folivore, frugivore, insectivore), most primates use one or more food types beyond their primary one. Among lemurs, folivores tend to have a complicated, long gastrointestinal tract with an enlarged cecum, shearing teeth, and microbiome adaptations to foliage, while frugivores have simple teeth and guts and fast gut passage. Yet frugivores often eat some leaves, and folivores eat some fruit, and little is known about the selection rules they follow within each food type. We quantified diet and food chemistry for two sympatric rainforest lemurs: a cathemeral frugivore (brown lemur, Eulemur fulvus) and a diurnal folivore (diademed sifaka, Propithecus diadema) over 18 and 13 months. Brown lemurs ate 78.3% fruit and 13.0% leaves; sifakas ate 52.8% leaves and 37.9% fruit/seed; both ate fruit/seed most in the resource‐abundant season, increasing leaf/flower consumption in the lean season. Both had diverse diets (128 and 81 plant species) but selected almost entirely different species; however, within fruit and leaf categories, their foods overlapped substantially in nutritional content. They were more selective in their secondary foods: sifakas selected higher‐energy fruits and brown lemurs selected leaves higher in protein and minerals. This indicates a balancing function: frugivores selecting leaves strategically to compensate for low‐protein, low‐mineral fruit and folivores selecting fruit/seed to compensate for low‐energy leaves. That said, it is puzzling why sifakas ignored some leaf species eaten by brown lemurs that were high in protein and minerals—this suggests these nutrients are not prioritized or limiting for sifakas. Other factors likely contribute to the mutual exclusivity in food selection, particularly plant secondary metabolites not measured here or the (poorly‐understood) metabolic costs of eating nutrients in excess. More research is needed to fully understand food choices, how these promote niche differentiation, and their consequences for animals, communities, and ecosystems.